2015
DOI: 10.1177/0895904815568936
|View full text |Cite
|
Sign up to set email alerts
|

Educational Policy Implementation Revisited

Abstract: This article outlines the rationale for this special issue on educational policy implementation and provides an overview of the articles in this issue. In addition to summarizing each article, we point out how the findings from the different contributions complement, challenge, and complicate not only the findings and conclusions from other works in this issue, but also insights articulated by Honig (2006) and Odden (1991). We conclude with a discussion of the implications from these articles for educational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 7 publications
0
38
0
1
Order By: Relevance
“…The OECD has also analysed and considered the focus of policy implementation, given its mandate which aims to promote "better policies for better lives". As part of this remit, the organisation has explored the role of implementation, or the political economy of reform and how to "make reform happen" (Wurzburg, 2010 [49] ; Gurría, 2015 [6] ; Pont, 2008 [8] ). Selected education projects tackling implementation include support on education reform implementation in Mexico (OECD, 2010 [16] ; OECD, 2011 [50] ), Norway (OECD, 2012 [51] ) and in Wales (OECD, 2017 [52] ), and work on the governance of education systems (Burns and Köster, 2016 [22] ; Burns, Köster and Fuster, 2016 [10] ).…”
Section: Actionable Framework For Policy Makersmentioning
confidence: 99%
See 1 more Smart Citation
“…The OECD has also analysed and considered the focus of policy implementation, given its mandate which aims to promote "better policies for better lives". As part of this remit, the organisation has explored the role of implementation, or the political economy of reform and how to "make reform happen" (Wurzburg, 2010 [49] ; Gurría, 2015 [6] ; Pont, 2008 [8] ). Selected education projects tackling implementation include support on education reform implementation in Mexico (OECD, 2010 [16] ; OECD, 2011 [50] ), Norway (OECD, 2012 [51] ) and in Wales (OECD, 2017 [52] ), and work on the governance of education systems (Burns and Köster, 2016 [22] ; Burns, Köster and Fuster, 2016 [10] ).…”
Section: Actionable Framework For Policy Makersmentioning
confidence: 99%
“…Experts have been advocating for governments to invest in their educator workforce (OECD, 2010 [16] ; Wurzburg, 2010 [49] ; Hargreaves and Fullan, 2012 [87] ), including in developing school leaders and teachers' skillset, but also their capacity to implement reforms. Stakeholders' capacity can be built both in the medium term (e.g.…”
Section: Capacitymentioning
confidence: 99%
“…Hence, effective results of an education reform whose aim is transforming schools into more beneficial institutions depend not only on its conceptual foundations or its proper design, but also on its successful realization by principals who lead the reform in their schools (McDonald, 2014;Young & Lewis, 2015). Therefore, school principals may be the linchpin of effective implementation of any school-level reform (New Leaders, 2013).…”
Section: Theoretical Framework Principals' Role In Reform Implementationmentioning
confidence: 99%
“…Implementing an education reform is a complex continuous endeavor (McDonnell & Weatherford, 2016;Young & Lewis, 2015). A large body of literature has shown that a central determinant for the effectiveness of school reform is the way in which the reform is implemented (Ramberg, 2014).…”
Section: Theoretical Framework Principals' Role In Reform Implementationmentioning
confidence: 99%
“…However, research demonstrates that policies are not always implemented as intended or with fidelity (Cohen and Hill, 2001;Correnti and Rowan, 2007;Kennedy 2005;Rigby, Woulfin & März, 2016;Rowan and Miller, 2007). According to Young and Lewis (2015), "variation in implementation is the rule, not the exception" (p. 14). Given the complex, individualized nature of special education law, it is not surprising that it is an area of law where variation occurs frequently (O'Laughlin, L., & Lindle, J. C., 2014).…”
Section: Introductionmentioning
confidence: 99%